Sports math an introductory course in the mathematics of sports science and sports analytics - Minton, Roland B. 1956- (Textbooks in mathematics (Boca Raton, Fla.), 2017)
"This is a textbook for a course in sports science or sports analytics. The opening section is on standard mathematical sports examples which are physics-related, including projectile motion and rotational motion. A middle section introduces several rating systems. Many of these matrix-based systems were made famous by the soon-defunct college football BCS system. The final section of the book contains statistical analysis of sports, taking in Moneyball-like techniques. Game strategies and player evaluation are the main goals of these chapters."--Provided by publisher.